Distributed Extended State Observer-Based Formation Control of Multiple Flight Vehicles - WANG Xianzhi, LI Guofei, CHANG Ya’nan (Shanghai Jiaotong Daxue xuebao)
In order that the flight vehicle group could form the expected formation, the “leader-follower” formation control law is investigated. First, the distributed extended state observer (DESO) is designed such that the followers could estimate the virtual leader’s position and velocity. Then, the expected positions of the followers are calculated based on the observer outputs and the nominal formation configuration. A dynamic surface control-based position tracking control law is designed for the followers to track the expected positions. Based on the Lyapunov theory, the stability of the proposed method is proved, while numerical simulations validate the effectiveness. The DESO could estimate both the virtual leader’s position and velocity via only the position observations. The method proposed guarantees that the orientation of the formation is consistent with the direction of the virtual leader’s velocity.